2023
DOI: 10.22159/ijpps.2023v15i5.47280
|View full text |Cite
|
Sign up to set email alerts
|

Genus Lepidagathis (Acanthaceae): Review of Its Ethanobotany, Phytochemistry and Pharmacological Potential

Abstract: Almost all societies have employed medicinal plants as a source of medicine. Due to their natural origin, low cost, and lack of side effects, traditional medicinal plants have become increasingly popular over the past few decades. The Vedas and the Bible both mention the common usage of herbal medicines and healthcare products. People have used medicinal plants for thousands of years to flavour and preserve food, cure health problems, and prevent disease. Acanthaceae plant species are valued for their cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Wakuma et al (2021) showed that the methanolic leaf extract and solvent fractions of H. forskaolii have antidiabetic, and antioxidant activity that provides scientific support for the local use of the plant in the treatment of diabetes. Dhanalakshmi and Thangadurai (2021) and Ponnusamy and Balakrishnan (2023) evaluated the antioxidant and anticancer activities of Lepidagathis pungens and identified a few biomedical uses of a few significant species within this significant plant family.…”
mentioning
confidence: 99%
“…Wakuma et al (2021) showed that the methanolic leaf extract and solvent fractions of H. forskaolii have antidiabetic, and antioxidant activity that provides scientific support for the local use of the plant in the treatment of diabetes. Dhanalakshmi and Thangadurai (2021) and Ponnusamy and Balakrishnan (2023) evaluated the antioxidant and anticancer activities of Lepidagathis pungens and identified a few biomedical uses of a few significant species within this significant plant family.…”
mentioning
confidence: 99%